Myoepithelial differentiation subsequent to giant basal cell carcinoma in the left face - Zhao, Yu-Kun; Chen, Yan-Bin; Chen, Li-Li; Li, Yang; Li, Xiang; Luo, Di-Qing (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
A 71-year-old man presented with 11 years of asymptomatic facial ulcer that was a tiny papule initially, then increased in size slowly with central erosion over the years. A few months before the presentation, a subsequent papule in the previous lesion presented which was asymptomatic and enlarged in size gradually. His medical and family histories were unremarkable. Cutaneous examination revealed that an ulcerated plaque of about 10 cm × 6 cm in across located on the left cheek, associated with irregularly raised circular hyperpigmented papules around and scars on the centre, and a red erosive nodule-plaque about 2.5 cm in diameter localized on the left lower quadrant of the ulcer near the middle of mandible (Figure 1). Computed tomography scan showed no lymphatic metastasis. The lesion was completely excised without recurrence in a 9-year follow-up.